EROSI IMAN DI ERA DISRUPSI: REINTERPRETASI IRTIDĀD DALAM QS. AL-MĀ'IDAH: 54 MELALUI VARIASI QIRĀ'ĀT - Siti Amelia; Hananajma Muharromah; Naima Aziza; Najib Irsyadi (PT. Hasba Edukasi Mandiri, 2026)
This article investigates how the variation of Qur'anic readings (qirā'āt) in QS. al-Mā'idah: 54 opens a new semantic space for reinterpreting the gradual erosion of religious commitment among contemporary Muslim netizens a phenomenon termed